2014
DOI: 10.1103/physrevb.90.245423
|View full text |Cite
|
Sign up to set email alerts
|

High harmonic generation in undoped graphene: Interplay of inter- and intraband dynamics

Abstract: We develop a density matrix formalism in the length gauge to calculate the nonlinear response of intrinsic monolayer graphene at terahertz frequencies. Employing a tight-binding model, we find that the interplay of the interband and intraband dynamics leads to strong harmonic generation at moderate field amplitudes. In particular, we find that at low temperature, the reflected field of undoped suspended graphene exhibits a third harmonic amplitude that is 32% of the fundamental for an incident field of 100 V/c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
142
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(149 citation statements)
references
References 47 publications
4
142
2
1
Order By: Relevance
“…The strong many‐body interaction and distinctive electronic properties in 2D materials make them promising in HHG application. Indeed, HHG was demonstrated in graphene thanks to their unique electronic properties . In terms of TMDs, Saynatjoki et al reported a fourth‐order harmonics in monolayer MoS 2, and HHG up to 13th order was demonstrated by Liu et al in MoS 2 (Figure D) .…”
Section: Nlo Processes In Tmdsmentioning
confidence: 93%
“…The strong many‐body interaction and distinctive electronic properties in 2D materials make them promising in HHG application. Indeed, HHG was demonstrated in graphene thanks to their unique electronic properties . In terms of TMDs, Saynatjoki et al reported a fourth‐order harmonics in monolayer MoS 2, and HHG up to 13th order was demonstrated by Liu et al in MoS 2 (Figure D) .…”
Section: Nlo Processes In Tmdsmentioning
confidence: 93%
“…Theoretical studies of strong-field excitations in layered materials have also been performed in graphene [142,143] and predict a strong harmonic generation in these materials. [142] To reach the necessary ultrastrong fields, Ref. [144] suggests to harness plasmonic field enhancement created by nanostructuring.…”
Section: New Materialsmentioning
confidence: 99%
“…Several works in this direction show indeed that ac transport in graphene is a rich subject. Studies include quantum pumping [8][9][10][11][12], nonlinear electromagnetic response [13][14][15][16][17][18], and photon-assisted tunneling phenomena [19][20][21][22][23][24][25]. In theoretical investigations for low doping (Fermi energy E F close to the Dirac point) and high frequencies , with E F and of comparable magnitude (we put = 1), a true quantum mechanical description becomes necessary.…”
Section: Introductionmentioning
confidence: 99%